Resiliência e sustentabilidade da agricultura de sequeiro sob instabilidade pluviométrica na Paraíba - Lessa, Laura Cunha Rebouças (2023)
One of the main climatic characteristics of the Brazilian semi-arid region is instability in rainfall both spatially and temporally. The state of Paraíba has 84% of its municipalities recognized as belonging to the semi-arid region. In that state, most farmers practice rainfed agriculture, defined as dependent on rain for its full development. The crops studied in the research are rice, beans, cassava, and corn. The specific objectives are: a. identify the behavior of rainfall in Paraíba between the years 1901 and 2020 and try to fit them into three periods: dry, normal, and rainy; B. to design an instrument capable of measuring the existing synergy between the variables that define the production of rainfed crops, between 1945 and 2020; ç. assess the existence of resilience to the occurrence of water stress in agricultural production; d. estimate the productivity and aggregate income per hectare of the crops studied; and. show the trajectories of aggregate productivity and aggregate income per hectare of the crops studied between the years 1945 and 2020; f. evaluate the effect of rain on productivity projections and aggregate income per hectare, simulating the evolution of these variables for the decade from 2021 to 2030, based on the scenarios of occurrence of rains in the defined periods; g. to assess whether the trajectories of productivity and aggregate income per hectare associated with the production of these crops were sustainable in the evaluated period. The data used are of secondary origin and taken from the Municipal Agricultural Production, Statistical Yearbooks of the IBGE, and the database of the National Oceanic and Atmospheric Administration. The factorial analysis methodology is used for the construction of an Index of Resilience of the Dryland Crops (IRLS), used to evaluate the behavior of the dryland production of Paraíba and to verify if, throughout the period studied, this production was resilient to the stresses provoked by droughts. To draw the trajectories of productivity and aggregate income per hectare, the research used the Box and Jenkins method. To assess whether these variables were sustainable over the period studied, the researchers estimated the geometric rates of instantaneous growth. It was detected that the state presented high rainfall variability in the series of 120 years analyzed, in which 40 years were dry, 49 were normal, and 31 were rainy. It verified the existence of resilience of farmers who practice rainfed crops in the face of rainfall instabilities that occurred in Paraíba during the evaluated period. The evidence also showed that rain interferes in the forecast of aggregate productivity, but that it does not cause direct interference in the forecast of aggregate income per hectare of the crops studied. The general conclusion of the research is that farmers managed to maintainsustainable agricultural production in Paraíba, even under the effects of high rainfall instability between 1945 and 2020.